Genetic divergence of jesso-balam rice (Oryza sativa L.) of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2015)
In total 27 genotypes of Jesso-Balam pure line rice germplasm were studied for fourteen morpho-physiological and four physico-chemical characters at Bangladesh Rice Research Institute, during T. Aman 2009 and T. Aman 2011 seasons. According to principal component scores, the two-dimensional scatter diagram (Z1-Z2) has apparently distributed the genotypes into seven clusters. According to Mahalanobis D2 statistic for the studied characters, the genotypes were clubbed into seven groups. The highest number of genotypes (6) were included in clusters I and III and the lowest two (2) in cluster V and VII. It was also revealed that no duplicate was existed among the genotypes. The intra-cluster distance was maximum (0.77) in cluster III and minimum (0.28) in cluster VII, while the maximum intercluster distance (28.37) was observed between the clusters III and IV and the minimum (2.49) between the clusters I and VII. The cluster V has produced the highest means for plant height (148.18 cm), straw yield per hill (39.97 g), panicle length (28.14 cm) and protein content (9.61%). But, the cluster IV has showed the highest means for seedling height (69.5 cm), flag and penultimate leaf area (1059.5 cm2), culm diameter (5.8 cm), filled grain number per panicle (3.64), grain length (8.63 mm) and 1000-grain weight (21.78 g), while the cluster VII had the highest means for grain yield per hill (31.27 g) and effective tiller number per hill (13.5) and the lowest mean for days to maturity (144). Therefore, the genotypes of cluster V need to be crossed with the genotypes of cluster IV or cluster VII, for developing new Balam rice with maximum other good characters. Finally, it could be concluded that the studied Jesso-Balam pure lines germplasm is a good source of valuable genes.Int. J. Agril. Res. Innov. & Tech. 5 (1): 22-27, June, 2015